2015
DOI: 10.1080/1062936x.2015.1085896
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure–permeability relationships at various pH values for acidic and basic drugs and drug-like compounds

Abstract: Absorption in gastrointestinal tract compartments varies and is largely influenced by pH. Therefore, considering pH in studies and analyses of membrane permeability provides an opportunity to gain a better understanding of the behaviour of compounds and to obtain good permeability estimates for prediction purposes. This study concentrates on relationships between the chemical structure and membrane permeability of acidic and basic drugs and drug-like compounds. The membrane permeability of 36 acidic and 61 bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
3
18
1
Order By: Relevance
“…For instance, the permeability coefficients (log P e ) of indole and coumarin are reported as −4.50 and −4.55, respectively, which are considered fast (Fujikawa et al, 2007 ). In contrast, doxepin, whose permeability coefficient is < −6 in acidic solutions (which matches our experimental condition for using doxepin hydrochloride in the donor well), is categorized as slow permeation (Oja and Maran, 2015 ). Meanwhile, the performance of l -tryptophanamide is moderate to slow with a permeability coefficient of −5.56 (Fujikawa et al, 2007 ).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…For instance, the permeability coefficients (log P e ) of indole and coumarin are reported as −4.50 and −4.55, respectively, which are considered fast (Fujikawa et al, 2007 ). In contrast, doxepin, whose permeability coefficient is < −6 in acidic solutions (which matches our experimental condition for using doxepin hydrochloride in the donor well), is categorized as slow permeation (Oja and Maran, 2015 ). Meanwhile, the performance of l -tryptophanamide is moderate to slow with a permeability coefficient of −5.56 (Fujikawa et al, 2007 ).…”
Section: Resultssupporting
confidence: 69%
“…The thickness of the unstirred water layer, for example, is a critical parameter, especially for large drug molecules; in some circumstances, it can be a rate-limiting step (Wohnsland and Faller, 2001 ; Nielsen and Avdeef, 2004 ). The pH of the drug solution is another important factor, as the neutral form of a compound regularly has a larger permeability than the ionic one (Oja and Maran, 2015 ). Besides, the in vivo absorptive sink condition (e.g., a pH gradient at the two sides of the membrane, blood flow, and serum proteins) has also been considered, which led to the development of the double-sink PAMPA method, as a variant (Avdeef, 2003 ; Avdeef et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, PAMPA permeability is sensitive to the assay conditions (vide supra). To warrant data consistency and to minimize the variations in assay conditions among different data sources [34,38,39,40,41,42,51,55,75,77,78,79,80], only those molecules assayed by Oja and Maran [39,41,42] were selected in this study since they generated the largest quantity of data. If there were two or more available efflux ratio data for a given compound and in close range, the average values were then taken in order to warrant better consistency.…”
Section: Methodsmentioning
confidence: 99%
“…As such, in silico approaches play an increasing role in ADME/Tox profiling [27]. In fact, numerous qualitative structure–activity relationship (QSAR) models have been developed to predict PAMPA permeability [7,23,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of studies reported models for PAMPA permeability in literature. 3135 Most studies either use a different kind of assay to measure PAMPA permeability or use small datasets comprising a few hundred compounds. Searching by keyword “PAMPA” resulted in a total of 935 assay records and 1015 measurements on ChEMBL.…”
Section: Resultsmentioning
confidence: 99%